The relationship of provider organizational status and erythropoietin dosing in end stage renal disease patients. - de Lissovoy, G; Powe, N; Griffiths, R; Watson, A; Anderson, G; Greer, J; Herbert, R; Eggers, P; Milam, R; Whelton, P (1994)
Controversy exists as to whether provider organizational characteristics such as profit status and setting are associated with the content of medical care or efficiency with which care is rendered. Following FDA approval of human recombinant erythropoietin (EPO) for use in clinical practice, Medicare approved coverage for beneficiaries in its end stage renal disease program and established a fixed payment per dose. Because cost of EPO administration varied positively with dose, providers could realize larger profit with prescription of smaller doses. We used Medicare claims data to assess EPO use by renal dialysis providers one year after FDA approval (June 1990) as a function of provider ownership (for-profit, not-for-profit, government agency) and setting (hospital-based, free-standing). Mean dose of EPO was 236 units greater (P = 0.0001) for not-for-profit freestanding facilities, 593 units greater (P = 0.0001) for government facilities, and 555 units greater for not-for-profit hospitals (P = 0.0001) than among for-profit freestanding providers. With fixed payment per dose of EPO, for-profit, freestanding providers prescribed EPO more often and administered smaller doses than not-for-profit or government providers, behavior that is consistent with profit maximization.